1989
DOI: 10.1507/endocrj1954.36.681
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary Aldosteronism with Chronic Renal Failure Undergoing Hemodialysis Treatment.

Abstract: A 56-year-old man with primary aldosteronism and chronic renal failure undergoing hemodialysis is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…PRA remains in the normal range in 8.8-18.5% of patients with primary aldosteronism [2,11]. In previous reports (table 1), low PRA was noted in only 3 cases [16,19,22]. Iyori et al [16] suggested that renin secretion might be affected by the balance of two factors, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…PRA remains in the normal range in 8.8-18.5% of patients with primary aldosteronism [2,11]. In previous reports (table 1), low PRA was noted in only 3 cases [16,19,22]. Iyori et al [16] suggested that renin secretion might be affected by the balance of two factors, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, in primary aldosteronism with chronic renal failure, the serum potassium level seems to be determined by the balance of the augmentation and the suppression of potassium excretion by excess aldosterone and renal failure, respectively3, 5).…”
Section: Discussionmentioning
confidence: 99%
“…In case of primary aldosteronism with chronic renal failure, there is difficult to be diagnosed because hypertension is frequently associated with chronic renal failure. A few cases with primary aldosteronism accompanying chronic renal failure or end stage renal disease have been reported3-5). Two cases of primary aldosteronism with chronic renal failure6, 7) and one case with autosomal dominant polycystic kidney disease8) have been reported in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Spironolactone is a nonselective MR antagonist with an incidence of gynecomastia of approximately 7 % for doses at 50 mg/day and of more than 50 % for doses higher than 150 mg/day. Matsuda and colleagues [133] found that fecal potassium excretion in an anuric patient with PA and hypokalemia decreased while serum potassium increased after administration of spironolactone 50 mg/day. Eplerenone is a selective MR antagonist with 60 % of the potency of spironolactone and a shorter half-life but similar antihypertensive efficacy [134].…”
Section: Adrenalectomymentioning
confidence: 98%